SUFI HEALING PRAKTEK PENGOBATAN SPIRITUAL DI DESA CANGKREP KABUPATEN PURWOREJO - Syaifan Nur (UIN Sunan Kalijaga Yogyakarta, 2015)
The Sufi healing is an alternative therapy model which is practicing by adopting the practices and values of tasawuf as a medium of healing/anticipation. This therapy is common in the society, i.e. indeveloping Sufism tradition. The practical tasawuf practices, such as sholat, dzikir, tafakur (meditation), are not just rituals without meaning; however, in this Sufi practices, there is healing potencies to the illness that cannot be cured by modem medical world, such as cancer, stroke, many mental and psychological illnesses. The basic principle in the Sufi healing is the cure is only come from Allah the all healer. This writing tries to examine healer practice using Sufi model practicing by Kyai Tamo, a society leader who is active in Sufi world. This kyai who is living in Purworejo tries to introduce tasawuf to society by Sufi healing. This healing practice by Kyai Sutamo seems appealing to society, so that his practical place always filled by patients who are came by many kinds of illnesses